Resistensi antibiotik pada rantai pasok pangan: tren, mekanisme resistensi, dan langkah pencegahan - Muhammad Alfid Kurnianto; Fathma Syahbanu (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The emergence and spread of antibiotic-resistant bacteria along the food chain is a serious global health problem. The food chain provides various important transmission mediums in developing antibiotic resistance traits through direct or indirect contact. This review focuses on the phenomena and mechanisms of formation, the relationship with the food chain, the effects of food processing, and the impact and prevention of antibiotic resistance. This study shows that food plants and animal livestock are the main reservoirs of antibiotic-resistant bacteria. Antibiotic-resistant bacteria in food are generally commensal, foodborne (pathogenic and non-pathogenic), or emerging bacteria. Some examples of food-related pathogenic bacteria known globally are the Enterobacteriaceae group, such as Salmonella spp., E. coli, Shigella spp., K. pneumonia, and Enterobacter spp. Each bacterium has a different prevalence and pathogenicity level depending on the country's geographical location, resources, and status. In general, developing countries have a greater risk of spreading resistance than developed countries because of the high use of antibiotics in various fields of activity. Antibiotic-resistant bacteria develop resistance through transmission after consumption or during food processing. Food processing triggers genetic and physiological adjustments of bacteria that cause adaptation and cross-protection mechanisms that result in bacterial cells that are more resistant or tolerant to stress. In addition, bacterial cells damaged by the processing process can also spread resistant genes to the environment, triggering gene transfer through horizontal gene transfer. In preventing the spread of bacterial resistance, which has prepared preventive measures through a global action plan must be followed by developed and developing countries that include the human, animal, and environmental sectors.